Studi Kritis Pemikiran Tokoh Sosiologi Terhadap Pendidikan Islam - Maysa Latifa; Yasinta Nurul Hidayat; Yuliana Yuliana; Januar Januar (Concept: Journal of Social Humanities and Education, 2024)
The purpose of this discussion is to find out the thoughts of educational sociologists Emile Durkheim, Aguste Comte, Max Weber, Karl Max, and George Simmel regarding Islamic education. This discussion uses the library research method using data sources from journals and books related to the discussion theme. The research results showed that educational sociology figures such as Emile Durkheim, Aguste Comte, Max Weber, Karl Max, and George Simmel were sociological figures from the classical era. Emile Durkheim pioneered the development of sociology through research on societal institutions and social processes as well as his thoughts on Islamic education. Aguste Comte stated that sociology must be based on observation, comparison, experiments and historical methods. Max Weber, he introduced the vestehen (understanding) approach, which consists of exploring the values, beliefs, goals and attitudes that guide people's behavior which gives rise to social behavior. Karl Max stated that sociology can be used as a weapon to liberate society from the capitalist system so that a classless society can be achieved, and according to George Simmel society is a process that is ongoing and continuously developing. So, the thoughts of sociological figures regarding education are that schools cannot be separated from society, cooperation between schools and community figures needs to be formed, the child socialization process needs to be improved so that children are able to grow and develop in society.